Digital transformation in organizational health and safety to mitigate Burnout Syndrome - Sanchez-Segura, María-Isabel; Dugarte-Peña, German-Lenin; Medina-Dominguez, Fuensanta; Amescua Seco, Antonio; Menchen Viso, Rosa (Frontiers in Public Health, 2023)
Burnout syndrome affects 10% of workers and was declared by the World Health Organization in 2000 as an occupational risk factor. It causes therefore a decrease in productivity and an increase in costs since it can lead to sick leave. Some speak of Burnout Syndrome as an epidemic that ravages work environments and whose spread is not so difficult to palliate and identify in time, and whose impact is not easy to measure, generating different types of risks in the business: from the possibilities of losing human talent to the decrease in productivity in terms of performance and the quality of life of working people. Because the Burnout problem is complex, it must be approached from a creative, innovative, and systemic point of view, i.e., no different results can be expected if the problem is approached in the traditional way. This paper describes the experience in which a group of people was challenged to propose a creative idea to identify, prevent, or mitigate Burnout Syndrome in people and organizations, based on the implementation and use of technological tools and software. The guideline was that the proposals should be creative and feasible from an economic and organizational point of view. Twelve creative projects, including the analysis, design and management and control plans were received. In this paper we present a summary of the creative projects presented to the challenge and how we envision the impact that those proposals may have in the OHS field improvement.